Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1007/s11307-009-0278-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2β-Carbomethoxy-3β-(4-[18F]Fluorophenyl)Tropane and N-(3-[18F]Fluoropropyl)-2β-Carbomethoxy-3β-(4-Fluorophenyl)Nortropane, Tracers for Imaging Dopamine Transporter in Rat

Abstract: Structural modifications of [(18)F]beta-CFT significantly changed its biological properties, as shown by [(18)F]beta-CFT-FP. [(18)F]beta-CFT is a suitable tracer for both preclinical and human PET studies, but [(18)F]beta-CFT-FP is less suitable as a PET tracer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…These parallel studies provide a good demonstration of the strengths and weaknesses of different methods in radiopharmacological studies. Overall, the distribution of 18 F activity in rats after [ 18 F]CFT injection was in good agreement with our earlier preliminary studies [5,8] and with studies using [ 3 H]CFT [19,35]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These parallel studies provide a good demonstration of the strengths and weaknesses of different methods in radiopharmacological studies. Overall, the distribution of 18 F activity in rats after [ 18 F]CFT injection was in good agreement with our earlier preliminary studies [5,8] and with studies using [ 3 H]CFT [19,35]. …”
Section: Discussionsupporting
confidence: 91%
“…A report on the ability of [ 18 F]CFT to reflect nigral dopaminergic cell loss in a rat model of Parkinson's disease [7] as well as a study comparing the brain accumulation, metabolism, and kinetics of [ 18 F]CFT and [ 18 F]CFT-FP [8] have shown that [ 18 F]CFT can be used to image DAT in rats. The suitability of [ 18 F]CFT as a radioligand for in vivo studies of DAT in humans has been evaluated [9], and [ 18 F]CFT has been used in human studies of Parkinson's disease [10-15], schizophrenia [16,17], and detached personality [18].…”
Section: Introductionmentioning
confidence: 99%